2012
DOI: 10.1001/archsurg.2012.1144
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Symptom Severity of Pelvic Floor Disorders in Women Who Report a History of Sexual Abuse

Abstract: Objective: To examine the effect of previous sexual abuse or assault (SAA) on symptom severity, quality of life, and physiologic measures in women with fecal incontinence or constipation. Design: A cross-sectional study of a prospectively maintained clinical database. Setting: A tertiary referral center for evaluation and physiologic testing for pelvic floor disorders. Patients: Women with fecal incontinence or constipation examined during a 6-year period. Main Outcome Measures: Symptom severity and quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
9
1
1
Order By: Relevance
“…The relation of fecal incontinence to sexual abuse may have more to do with symptom perception and severity. Imhoff et al found that women who have experienced sexual abuse or sexual assault have greater symptom severity for fecal incontinence, 17 again underscoring the importance of asking all patients about a history of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of fecal incontinence to sexual abuse may have more to do with symptom perception and severity. Imhoff et al found that women who have experienced sexual abuse or sexual assault have greater symptom severity for fecal incontinence, 17 again underscoring the importance of asking all patients about a history of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Causa danos profundos no bem-estar físico, sexual, reprodutivo, emocional, mental e social das vítimas 6 . Na violência sexual contra mulher a penetração vaginal está presente na maioria das agressões, de acordo com as literaturas nacional 4 e internacional 17 , submetendo-as ao risco de gravidez indesejada e infecções sexualmente transmissíveis (IST), incluindo o HIV e a hepatite viral 4 .…”
Section: Introductionunclassified
“…Next to the previously described methodologic challenges in diagnosing CAN in children, pathophysiologic differences between adults and children with FC could also play a role. As the association between CAN and FC is mostly described in adults with slow-transit constipation and pelvic oor dyssynergia [4][5][6][7][8][9][10] , these types of constipation are less commonly acknowledged in young children. It could also be hypothesized that constipation, as a symptom of CAN, will develop over time and the association in young children is therefore not present yet.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In adults suffering from functional defecation disorders, such as slow-transit constipation and pelvic oor dyssynergia, a possible association with child abuse has been described, with 12%-44% of patients with constipation reporting a history of physical or sexual abuse. [4][5][6][7][8][9][10] In addition, abused adult patients reported more severe symptoms of constipation 7 , decreased quality of life 7 and more frequent use of surgical strategies 8 as compared to patients with no history of child abuse. Early detection of abuse is therefore important in the work-up of both pediatric and adult patients with FC.…”
Section: Introductionmentioning
confidence: 99%